2016
DOI: 10.1038/srep38745
|View full text |Cite|
|
Sign up to set email alerts
|

Defective Acetylcholine Receptor Subunit Switch Precedes Atrophy of Slow-Twitch Skeletal Muscle Fibers Lacking ERK1/2 Kinases in Soleus Muscle

Abstract: To test the role of extracellular-signal regulated kinases 1 and 2 (ERK1/2) in slow-twitch, type 1 skeletal muscle fibers, we studied the soleus muscle in mice genetically deficient for myofiber ERK1/2. Young adult mutant soleus was drastically wasted, with highly atrophied type 1 fibers, denervation at most synaptic sites, induction of “fetal” acetylcholine receptor gamma subunit (AChRγ), reduction of “adult” AChRε, and impaired mitochondrial biogenesis and function. In weanlings, fiber morphology and mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…This result suggested that ERK1/2 might have a role in maintaining myofiber mass in vivo [5]. Consistent with these results, developmental selective abrogation of Erk1 and Erk2 in myofibers induced muscle fiber loss and atrophy, with stronger effects in the type1-fiber-rich soleus (SOL) than in type 2-fiber-rich tibialis anterior (TA) and sternomastoid (STN) [6,7]. However, sustained ERK activation via selective myofiber expression of an MEK1 constitutively active mutant [8] or a Ras mutant that only activates the MEK-ERK1/2 pathway and not the PI3K-Akt pathway [9], failed to induce fiber hypertrophy.…”
Section: Erk1/2supporting
confidence: 67%
“…This result suggested that ERK1/2 might have a role in maintaining myofiber mass in vivo [5]. Consistent with these results, developmental selective abrogation of Erk1 and Erk2 in myofibers induced muscle fiber loss and atrophy, with stronger effects in the type1-fiber-rich soleus (SOL) than in type 2-fiber-rich tibialis anterior (TA) and sternomastoid (STN) [6,7]. However, sustained ERK activation via selective myofiber expression of an MEK1 constitutively active mutant [8] or a Ras mutant that only activates the MEK-ERK1/2 pathway and not the PI3K-Akt pathway [9], failed to induce fiber hypertrophy.…”
Section: Erk1/2supporting
confidence: 67%
“…2 c). No histological sign of denervation was observed, which was confirmed by following the expression of a set of genes known to be upregulated in the case of denervation (AChR-γ; Musk; Myogenin; Runx1) [ 46 ]. RT-q-PCR amplification of these genes showed that their expression was not significantly increased in MAP6 KO muscle compared to WT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the activation of the ERK1/2 pathway [ 194 , 204 ] is necessary for normal neuromuscular junctions [ 358 , 359 ], therefore, an intriguing possibility is that the transport-independent signaling functions of PIT1/2 are important for skeletal muscle function [ 204 , 333 ].…”
Section: Importance Of Dietary Phosphorus For Skeletal Muscle Heamentioning
confidence: 99%